Mobile Learning Using Cloud Computing - Dhanalakshmi, S; Suganya, S; Kokilavani, K (International Journal of Computer Sciences and Engineering, 2014)
Mobile cloud learning, a combination of mobile learning and cloud computing, is a relatively new concept that holds considerable promise for future development and delivery in the education sectors. With the mass popularity of 3G, WIFI wireless network and intelligent mobile terminal equipment (intelligent mobile phone, tablet computer, etc.), mobile learning has become one of the important ways of learning. But the traditional mobile learning mode has many disadvantages, and the mobile learning based on cloud computing is a good way to overcome the disadvantages. This paper first introduces the concept and cloud computing, then designs a structure of mobile learning system based on cloud computing and mobile learning architecture and how mobile learning differentiate from e-learning.